Optimalisasi Strategi Branding untuk Meningkatkan Pemahaman Brand Awareness terhadap Pelaku UMKM di Padukuhan Keruk I - Rio Gabriel Simamora; Roxy Yusewa; Hana Maren Tika; Alicia Roselyn; Joy Eunike A. Lumban Tobing; Riki Leonardus; Tomy; Marcelino Felix Yussanto; Marcelyta Evelyn Wibowo; Kristina Wulandari (Jurnal Atma Inovasia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving local economies, including in Padukuhan Keruk I, Banjarejo Village, Tanjungsari District, Gunungkidul Regency. However, limitations in marketing strategies, particularly branding, have led to low brand awareness of the products offered. This study focuses on a single MSME engaged in the snack food sector, which previously lacked a clear brand identity. The aim of this activity is to optimize branding strategies to enhance brand awareness through a design thinking approach. This method consists of five stages: empathize, define, ideate, prototype, and test. Data were collected through field observations, in-depth interviews with the business owner, and testing of brand designs. The results show that the business owner gained new insights into the importance of visual identity, brand storytelling, and social media utilization. The branding strategies—such as logo creation, packaging design, and the setup of online promotion channels—were successfully implemented. In conclusion, the design thinking approach proved effective in helping the MSME develop a branding strategy that fits its needs and gradually increases consumer awareness and product appeal.